2015
DOI: 10.1186/s12878-015-0035-3
|View full text |Cite
|
Sign up to set email alerts
|

Anemia in prospective blood donors deferred by the copper sulphate technique of hemoglobin estimation

Abstract: BackgroundPatients who require transfusion as part of their clinical management have the right to expect sufficient blood to be available to meet their needs and to receive the safest blood possible. Donor deferrals (disqualification) lead to loss of precious blood donors and blood units available for transfusion purposes. It is believed that a large majority of donor deferrals are due to temporal and correctable causes such as anemia in developing countries. It is therefore important to determine anemia among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 18 publications
6
10
0
1
Order By: Relevance
“…In this study, the most common anemias in Libreville blood donors were normocytic normochromic (39.4%) and normocytic hypochromic (23.6%). The highest prevalence of normocytic normochromic anemia observed in Libreville blood donors is consistent with the prevalence of 46.74% reported previously in Ghana [30]. The distribution of these two types of anemia was not identical in both sexes.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the most common anemias in Libreville blood donors were normocytic normochromic (39.4%) and normocytic hypochromic (23.6%). The highest prevalence of normocytic normochromic anemia observed in Libreville blood donors is consistent with the prevalence of 46.74% reported previously in Ghana [30]. The distribution of these two types of anemia was not identical in both sexes.…”
Section: Discussionsupporting
confidence: 89%
“…7780 All studies reported lower mean Hb concentrations (2.0–16.0 g/L) in venous blood analyzed by the CST compared with the reference (Fig. 2A).…”
Section: Resultsmentioning
confidence: 93%
“…2A). When applying the ±7% threshold for mean difference for the studies comparing the CST with the reference, two studies were within the threshold range 78,79 and two studies exceeded the ±7% bias 77,80 (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was highlighted in this study in which the study site that employed the copper sulfate hemoglobin screening protocol had significantly reduced serum ferritin levels compared to the other regions where automated hemoglobin estimations were employed. As the copper sulfate density-based hemoglobin screening procedure has been demonstrated to be fraught with low sensitivity in detecting negative iron balance,[ 19 20 ] blood donor recruitment centers should be encouraged to adopt hemoglobin meters for hemoglobin screening during mobile sessions to ensure adequate protection of prospective donors. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%